Analisis Kontribusi Pajak Daerah Dan Retribusi Daerah Dalam Upaya Peningkatan Pendapatan Asli Daerah Kabupaten Magelang Tahun 2019-2021 - Riris Nur Alia; Nuwun Priyono; Kartika Pradana Suryatimur (Jurnal Riset Akuntansi, 2023)
This study aims to examine the contribution of each regional tax and regional levy to Local Own Revenue (PAD) in Magelang Regency from 2019 to 2021. This study used a qualitative methodology and a descriptive approach. The findings of this study indicate that the receipt of local taxes and levies has fluctuated, and the contribution of regional taxes and levies to Regional original Revenue (PAD) is still low and not optimal. The highest contributing tax revenue from 2019-2021 was IDR 156,886,789,664 or 37.6% in 2019. Meanwhile, the highest regional levy revenue in 2020 was IDR 27,049,700,014 or 8.2%. Therefore, the Magelang Regency Government needs efforts to increase Regional Original Revenue in order to support the function of regional autonomy, namely organizing government and development financing.